Automated Hypothesis Generation to Identify Signals Relevant in the Development of Mammalian Cell and Tissue Bioprocesses, With Validation in a Retinal Culture System - Toms, Derek; Al-Ani, Abdullah; Sunba, Saud; Tong, Qing Yun (Victor); Workentine, Matthew; Ungrin, Mark (Frontiers in Bioengineering and Biotechnology, 2020)
We have developed an accessible software tool (receptoR) to predict potentially active signalling pathways in one or more cell type(s) of interest from publicly available transcriptome data. As proof-of-concept, we applied it to mouse photoreceptors, yielding the previously untested hypothesis that activin signaling pathways are active in these cells. Expression of the type 2 activin receptor (Acvr2a) was experimentally confirmed by both RT-qPCR and immunochemistry, and activation of this signaling pathway with recombinant activin A significantly enhanced the survival of magnetically sorted photoreceptors in culture. Taken together, we demonstrate that our approach can be easily used to mine publicly available transcriptome data and generate hypotheses around receptor expression that can be used to identify novel signaling pathways in specific cell types of interest. We anticipate that receptoR, (available at https://www.ucalgary.ca/ungrinlab/receptoR) will enable more efficient use of limited research resources.